IMPACT OF PREHARVEST CHEMICAL APPLICATION ON PLUM (PRUNUS SALICINA L.) CV. SANTA ROSA QUALITY DURING STORAGE - S.N. KIRMANI; M. M. MIR; UMAR IQBAL; AARIFA JAN; KOUSAR JAVAID; A. R. MALIK; F. A. KHAN (The Bioscan, 2015)
An experiment was conducted to studythe influenceof preharvest application of some chemicals on various chemical parameters of plum (Prunus salicinaL.) cv. Santa Rosa under ambient storage conditions, involving pre harvest spraying withCaCl2(0.1, 0.3 and 0.5%), GA3(20, 40 and 60 ppm) and NAA(20, 40 and 60ppm)applied 20 and 10 days before the expected date of harvest. TSS (12.63%) and total sugars (8.80%) at the harvest time were reported to be maximum in response to GA3 (60 ppm) while as 0.5% CaCl2 resulted in highest ascorbic acid (7.18 mg/100g) and juice content (62.94%) which decreased during storage under all treatments. CaCl2at higher concentration of 0.5%proved to be the most effective treatment in retaining the fruit quality during the entire storage period recording highest means values fortotal sugars (9.05%), reducing sugars (8.04%), non-reducing sugars (1.47%), TSS (12.80%), titrable acidity (1.411), ascorbic acid (6.69 mg/100gm) and juice content (55.07%). Thus, it can be inferred from the study that CaCl2 (0.5%) was rated as most acceptable and superior, over all the other treatments in term of quality parameters observed during ambient storage.